Proceedings of International Conference on Wireless Communication ICWiCom 2017 - Vasudevan, Hari.; Deshmukh, Amit A.; Ray, K. P.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
The volume comprises best selected papers presented at International Conference on Wireless Communication (ICWiCOM) which is organized by Department of Electronics and Telecommunication Engineering of D J Sanghvi College of Engineering. The volume focusses on narrowed topics of wireless communication like signal and image processing applicable to wireless domain, networking, microwave and antenna designs, tele-medicine systems, etc. The papers are divided into three main domains like, networking, antenna designs and embedded systems applicable to the communication domain. The content will be helpful for Post-Graduate and Doctoral students in their research.h.
Preface -- About the Editors -- Conference Organizing Committee -- Table of Contents -- 35 Papers -- Author Index.
Keywords: Telecommunication; Signal processing; Artificial intelligence; Communications Engineering, Networks; Signal, Speech and Image Processing; Artificial Intelligence